UNDERSTANDING THEOLOGICAL INTERPRETATION IN TAFSIR DEPARTEMEN AGAMA REPUBLIK INDONESIA PRINTED 1996-1997 - Masri Mansoer (Peminat Ilmu Ushuluddin, 2022)
This paper aims to discuss the understanding of Islamic theology in Tafsir Departemen Agama Republik Indonesia. This paper mainly discussed the pattern of interpretation of the verses found in the Tafsir Departemen Agama Republik Indonesia, especially in interpreting the verses of kalam used as arguments by the Mutakalimīn. The primary sources were Tafsir Departemen Agama Republik Indonesia. In contrast, the secondary sources were works from rational and traditional mainstreams. This study find that several verses of the Quran were used as Naqlī arguments by rational and traditional mainstreams, which the Ministry of Religious Affairs then interpreted. This paper shows that the interpretation of the verses in the Tafsir tends to be somewhat closer to the rational-Mātūrīdīyah Samarkand style of thought, not the Muʿtazilaʾs rationale. On the other hand, it has very little in common with traditional mainstream, such as Ashʿarīyah and Mātūrīdīyah Bukhārā.